Identification of a de novo NLRP3 gene variation in an Italian Behçet syndrome patient. (10th June 2019) - Padula, Maria Carmela; Leccese, Pietro; Lascaro, Nancy; Padula, Angela Anna; Carbone, Teresa; Martelli, Giuseppe; D'Angelo, Salvatore
Abstract: A novel nonsynonymous variation of NLRP3 was identified in an Italian patient with Behçet syndrome using both bioinformatics and molecular methods. This variation was a thymine to guanine polymorphism responsible for the isoleucine to serine amino acid change at position 348. The novel variation was predicted to be a pathogenic allele.